Frequency of LV Thrombus Formation after Anterior Wall St-Segment Acute Myocardial Infarction - Sohail Rashid, Muhammad Saeed Afridi, Zain Mehmood Butt, Muhammad Suleman Khan, Rimsha Tauqir, Mattiur Rahman, Ashiqullah Arman, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the frequency of thrombus formation in LV post Anterior wall ST Segment elevation acute MI. Methodology: In this descriptive case series during the year 2018 we included 100 cases of age 40-70years of either gender presenting with STEMI planned to undergo Transthoracic echocardiography. Demographic information including name, age, gender, BMI, smoking and diabetes (BSR>186mg/dl) was also noted. Then patients were admitted in cardiology wards and were followed-up there. Then patients were discharged after 3days and were followed-up in OPD for one week. After one week, patients were evaluated on 2-D Transthoracic echocardiography and LV thrombus was labeled. The patients who had LV thrombus, were managed as per hospital protocol. Results: The mean age of patients was 56.68±8.59years. There were 90 (90%) males and 10 (10%) females. The mean BMI of patients was 24.54±3.49kg/m2. There were 43 (43%) smokers and 57 (57%) were non-smokers. There were 36 (36%) diabetics and 64 (64%) were non-diabetics. In this study, 63 (63%) underwent thrombolysis and 87 (87%) underwent primary PCI after STEMI. There were 7 (7%) cases who developed LV thrombus while 93 (93%) were remained free of LV thrombus. Concussion: Frequency of Left ventricular thrombus formation is low in our local population. Keywords: Left ventricular thrombus, anterior wall myocardial infarction, ST-segment elevation myocardial infarction, Transthoracic echocardiography